Challenges and Opportunities in the Digital Era in Building Accounting Professional Ethics - Maisyarah, Renny; Darma, Dito Aditia; Anggasari, Febyana; Nababan, Putri Enzelina; Mendrofa, Sabar Jaya; Aldian, M. Rizki; Vadia, Reni (International Journal of Economics (IJEC), 2024)
The digital era has brought about significant transformation in the accounting profession, offering greater convenience, efficiency, and accuracy through technologies such as artificial intelligence (AI), big data, blockchain, and automation. However, these technological developments have also given rise to complex ethical challenges, particularly in terms of financial statement integrity, data security, and transparency. This study aims to explore the challenges and opportunities faced by the accounting profession in building and maintaining professional ethics amidst advances in digital technology. Based on the literature review, the main challenges faced by accountants include data privacy and security issues, the potential for misuse of technology to manipulate financial statements, and the loss of subjective elements of professionalism due to automation. On the other hand, technology also provides opportunities to increase transparency of financial statements, strengthen supervision and audits, and enrich accountants' competencies in deeper data analysis. This study suggests the importance of ethics training that is more relevant to technological developments, as well as the wise use of technology to strengthen the principles of accountability and integrity in the accounting profession. The findings of this study are expected to provide insight for practitioners, educators, and policy makers in creating a more professional and ethical work environment in the world of digital accounting.